Trends in Outcomes of Major Intracerebral Haemorrhage in a National Cohort of Very Preterm Born Infants in Switzerland - Philip Thwaites; Cornelia Hagmann; Juliane Schneider; Sven M. Schulzke; Sebastian Grunt; Thi Dao Nguyen; Dirk Bassler; Giancarlo Natalucci (MDPI AG, 2023)
Background: Major brain lesions, such as grade 3 intraventricular haemorrhage (G3-IVH) and periventricular haemorrhagic infarction (PVHI) are among the main predictors for poor neurodevelopment in preterm infants. In the last decades advancements in neonatal care have led to a general decrease in adverse outcomes. Aim: To assess trends of mortality and neurodevelopmental impairment (NDI) in a recent Swiss cohort of very preterm infants with grade 3 intraventricular haemorrhage (G3-IVH) and periventricular haemorrhagic infarction (PVHI). Methods: In this retrospective population-based cohort study, rates of mortality, and NDI at 2 years corrected age were reported in infants born at 24-29 weeks gestational age (GA) in Switzerland in 2002-2014, with G3-IVH and/or PVHI. Results: Out of 4956 eligible infants, 462 (9%) developed G3-IVH (n = 172) or PVHI (n = 290). The average mortality rates for the two pathologies were 33% (56/172) and 60% (175/290), respectively. In 2002-2014, no change in rates of mortality (G3-IVH, p = 0.845; PVHI, p = 0.386) or NDI in survivors (G3-IVH, p = 0.756; PVHI, p = 0.588) were observed, while mean GA decreased (G3-IVH, p = 0.020; PVHI, p = 0.004). Multivariable regression analysis showed a strong association of G3-IVH and PVHI for both mortality and NDI. Death occurred after withdrawal of care in 81% of cases. Conclusion: In 2002-2014, rates of mortality and NDI in very preterm born infants with major brain lesions did not change. The significant decrease in mean GA and changing hospital policies over this time span may factor into the interpretation of these results.